Practice Services Between Sale and Purchase of Coffee Syari'ah Economic Perspective - Siti Afifah Nurullah (Journal of Nusantara Economy, 2022)
The purpose of this study is to find out how the practice of intermediary services for selling and buying coffee in Tanjung Aur Village, Maje District, Kaur Regency, and to find out how the Sharia Economic Law review is for the practice of intermediary services for buying and selling coffee in Tanjung Aur Village, Maje District, Kaur Regency. The type of research to be carried out is qualitative research. Informants were determined by purposive sampling technique. The informants in this study were coffee farmers and buying and selling intermediaries. The number of informants is 14 people. The study's results revealed that: (1) coffee intermediary services in Tanjung Aur Village were carried out between coffee farmers and buying and selling intermediaries. Farmers give power to intermediaries to sell the coffee they get to wholesalers or large buyers of agricultural products. After the coffee is sold, the farmer will receive the proceeds from the sale given by the intermediary. (2) Review of Sharia Economic Law on buying and selling coffee intermediary services in Tanjung Aur Village is illegal. As emphasized in Al-Qur'an As-Syu'ara verse 183, which means do not harm humans in their rights and do not run rampant on earth by causing damage, and following the rules of fiqh, namely harm should be eliminated. So an act that can cause harm or loss between one party and another is not permissible.   Tujuan dari penelitian ini yaitu untuk mengetahui bagaimana praktik jasa perantara jual beli kopi di Desa Tanjung Aur Kecamatan Maje Kabupaten Kaur dan untuk mengetahui bagaimana tinjauan Hukum Ekonomi Syariah terhadap praktik jasa perantara jual beli kopi di Desa Tanjung Aur Kecamatan Maje Kabupaten Kaur. Jenis penelitian yang akan dilakukan yaitu penelitian lapangan (field research) dengan menggunakan penelitian kualitatif. Informan ditentukan dengan teknik purposive sampling. Yang menjadi informan dalam penelitian ini adalah petani kopi dan perantara jual beli. Jumlah informan yaitu 14 orang. Hasil penelitian mengungkapkan bahwa: (1) Praktik jasa perantara jual beli kopi di Desa Tanjung Aur dilakukan antara petani kopi dan perantara jual beli. Petani memberikan kuasa kepada perantara untuk menjualkan hasil kopi yang mereka peroleh kepada pedagang besar atau pembeli hasil pertanian berjumlah besar. Setelah kopi terjual baru kemudian petani akan menerima hasil penjualan yang diberikan perantara. (2) Tinjauan Hukum Ekonomi Syariah terhadap praktik jasa perantara jual beli kopi di Desa Tanjung Aur hukumnya Haram atau tidak diperbolehkan. Sebagaimana yang ditegaskan dalam Al-Qur’an As-Syu’ara ayat 183 yang artinya Dan janganlah kamu merugikan manusia pada hak-haknya dan janganlah kamu merajalela di muka bumi dengan membuat kerusakan, dan sesuai dengan kaidah fiqih yaitu kemudharatan hendaklah dihilangkan. Sehingga suatu perbuatan yang dapat mendatangkan kemudharatan atau kerugian antara satu pihak dengan yang lain tidak diperbolehkan.